Short Videos, Big Impact: Strategic Competitive Advantage in the Attention Economy - Bagastya Christian Santoso (Jurnal Riset Multidisiplin Edukasi, 2026)
Short-form video has moved well beyond content format. In an attention economy where every second a user spends on a screen is a resource actively competed over the question is no longer whether a business needs to be on short-form platforms, but whether that presence can generate something competitors genuinely cannot replicate. This article answers that through a systematic literature review combined with platform-level analysis. The comparison of TikTok, Instagram Reels, and YouTube Shorts goes deeper than a feature list: each platform runs on a different algorithmic logic and content-distribution architecture, which means a strategy that works in one ecosystem tends to underperform when transplanted to another. The literature is also consistent on what actually produces durable advantage not production technology or posting frequency, but consistency of content and authenticity of voice. Unglamorous to talk about, which is precisely why they are so hard to copy. The Bali context adds a dimension the global literature largely skips. Local SMEs hold real content assets cultural specificity, craft processes, landscapes with documented appeal to global audiences. Yet the gap between that potential and what most businesses actually extract from these platforms remains wide. Not from lack of motivation. More from limited digital literacy, absent content infrastructure, and no strategic framework to work from. This article proposes a framework connecting attention economy theory, dynamic capabilities, and platform-based content strategy designed to be usable, not just citable.